Identifikasi Spesies Pinang (Areca catechu L.) dan Pemanfaatannya oleh Masyarakat Maluku Utara - Lintal Muna (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2021)
Areca catechu L. is a type of palm whose direct use is still limited to certain consumers. This plant is rich in benefits. The use of areca nut is different from one area to another. This study deserves to be researched, as information for the Indonesian people about the use of areca nut. This study aims to identify betel nut species and to assess the use of betel nuts by the people of North Maluku. This research was a qualitative research. This research was conducted in 3 locations, namely 1 location in Jailolo Selatan sub-district to be precise in Sukadamai Village, West Halmahera Regency and 2 locations in Tidore Islands, precisely in Gurabunga Village and Rum Village. This research was conducted in June-July 2019. The data collection technique was done by means of observation, interviews, and documentation. The data that has been collected is then analyzed using a plant identification book and matching it with several references from research journals, while for interviews used data reduction techniques, data display, drawing conclusions and verification. Based on the research results, there are 5 species of areca nut, namely the common areca nut, the pare areca nut, the round areca nut, the areca nut, and the areca palm. As for the use of areca nut by the people of North Maluku, namely as an ingredient for daily consumption (chewing) with lime and betel, itching medicine, appetite enhancer for children and adults, eye purifier, cleaning the tongue in toddlers, overcoming discomfort in children. mouths of adults, anti migraine, traditional events (weddings, ceremonies for inviting genies), medicine for people with liver disease, and washing wounds.